2009
DOI: 10.1111/j.1728-4465.2009.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiple Sampling Approaches to Measure Sexual Risk‐taking Among Young People in Haiti: Programmatic Implications

Abstract: No studies have examined the applicability of varying methods for identifying youth at high risk of unintended pregnancies and contracting HIV. This study compares sociodemographic characteristics and sexual behaviors of youth (ages 15-24) in Port-au-Prince, Haiti surveyed using three different study methodologies. The three study methodologies are compared in terms of their utility for identifying high risk youth and utility for program planning. The three study methodologies are: a representative sample of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In previous comparisons to household studies, the PLACE method captured individuals who reported higher sexual risk behaviors. [46] The PLACE Kenya study is the first time it has been possible to compare HIV prevalence obtained from the PLACE approach versus a household survey.…”
Section: Discussionmentioning
confidence: 99%
“…In previous comparisons to household studies, the PLACE method captured individuals who reported higher sexual risk behaviors. [46] The PLACE Kenya study is the first time it has been possible to compare HIV prevalence obtained from the PLACE approach versus a household survey.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology is based on epidemiology theory which indicates that there is often geographic clustering of HIV transmission (Grassly et al, 2001; Wasserheit and Aral, 1996; Weir et al, 2005) and has been described elsewhere (Weir et al, 2004). The PLACE method has been implemented in over 60 countries and has been shown to be more effective in capturing the individuals with riskier sexual behaviors compared to household surveys (Speizer et al, 2009; Tate et al, 2010; Weir et al, 2004). …”
Section: Methodsmentioning
confidence: 99%
“…Economic insecurity, ‘lamize’ or economic despair in Creole, has been reported to be associated with early initiation of sex and dependence on sexual relationships for survival among Haitian youth, where 15% of boys and 11% of girls who were sexually experienced report exchanging money for sex in the past 4 weeks (Speizer, Beauvais, Gómez, Outlaw, & Roussel, 2009). Lastly, the lack of opportunity to attend school may also provide children with more unstructured time to seek out risky sexual behaviors that may lead to HIV infection.…”
Section: Discussionmentioning
confidence: 99%